2017
DOI: 10.1128/aem.02821-16
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Staphylococcus aureus Dual-Species Biofilms Treated with Bacteriophage phiIPLA-RODI Depends on the Accompanying Microorganism

Abstract: The use of bacteriophages as antimicrobials against pathogenic bacteria offers a promising alternative to traditional antibiotics and disinfectants. Significantly, phages may help to remove biofilms, which are notoriously resistant to commonly used eradication methods. However, the successful development of novel antibiofilm strategies must take into account that real-life biofilms usually consist of mixed-species populations. Within this context, this study aimed to explore the effectiveness of bacteriophage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 47 publications
2
44
0
1
Order By: Relevance
“…In this scenario, bacteriophages appear to be an alternative strategy to treat biofilm-forming infections. Over the past few years, numerous studies have been carried out investigating the effectiveness of phages against mono-and dualspecies biofilm (Sillankorva et al, 2010;Chhibber et al, 2015;Gutierrez et al, 2015;Gonzalez et al, 2017;Melo et al, 2019). Many of these studies pointed to a notable dependency between the phages and the bacterial species involved on the biofilm for the efficacy of the phage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, bacteriophages appear to be an alternative strategy to treat biofilm-forming infections. Over the past few years, numerous studies have been carried out investigating the effectiveness of phages against mono-and dualspecies biofilm (Sillankorva et al, 2010;Chhibber et al, 2015;Gutierrez et al, 2015;Gonzalez et al, 2017;Melo et al, 2019). Many of these studies pointed to a notable dependency between the phages and the bacterial species involved on the biofilm for the efficacy of the phage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The lytic activity of bacteriophages was examined and confirmed by the CLSM. Disruption of the cell membrane due to lysis leads to penetration of propidium iodide stain, whereas live bacterial cells that are not lysed stain with SYTO ® 9 appear in green color (Ansari et al, 2015; Hu et al, 2015; González et al, 2017). The application of phages on MDR-bacterial pathogens present in the single species biofilms showed decreased biomass to almost 80%.…”
Section: Discussionmentioning
confidence: 99%
“…After 15 min incubation at room temperature in the dark, samples were washed with sterile saline for removing the excess dye and rinsed with water from the base of the support material. In order to minimize the air contact and maintain constant sample moisture conditions, a coverslip was used on the specimen (González et al, 2017). Due to the bacteriolytic activity of phages leads to the disruption of bacterial biofilm integrity and allows the propidium dye and appears in red color and live bacteria present in the biofilm appears in green color.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies have shown that staphylophages alone or in combination with other compounds can be effective for biofilm removal ( Son et al, 2010 ; Kelly et al, 2012 ). Quite recently, Gutiérrez et al (2015) isolated two virulent staphylophages, vB_SauM_ phiIPLA-RODI (phiIPLA-RODI) and vB_SepM_ phiIPLA-C1C (phiIPLA-C1C) that exhibited antibiofilm activity against both single-species and mixed-species biofilms formed by S. aureus ( Gutiérrez et al, 2015 ; González et al, 2017 ). Here, we set out to determine the ability of the aforementioned phages to penetrate biofilms formed by different species and strains, both sensitive and insensitive to the viruses.…”
Section: Introductionmentioning
confidence: 99%